2013
DOI: 10.1016/j.rppneu.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles, nanotechnology and pulmonary nanotoxicology

Abstract: The recently emergent field of Nanotechnology involves the production and use of structures at the nanoscale. Research at atomic, molecular or macromolecular levels, has led to new materials, systems and structures on a scale consisting of particles less than 100 nm and showing unique and unusual physical, chemical and biological properties, which has enabled new applications in diverse fields, creating a multimillion-dollar high-tech industry. Nanotechnologies have a wide variety of uses from nanomedicine, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 57 publications
2
45
0
4
Order By: Relevance
“…School 5 (S5) was the only school that cooked meals for children, which may be the source of such high levels of indoor UFP due to combustion activity associated with cooking (Zhang et al, 2012;Ferreira et al, 2013). The type of the outdoor environment may also exert influence on the potential UFP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School 5 (S5) was the only school that cooked meals for children, which may be the source of such high levels of indoor UFP due to combustion activity associated with cooking (Zhang et al, 2012;Ferreira et al, 2013). The type of the outdoor environment may also exert influence on the potential UFP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UFP have been associated with more severe toxicity when compared to fine and coarse particles due to their ability to penetrate cell membranes (Peters et al, 1997;Penttinen et al, 2001;Semmler et al, 2004;Carosino et al, 2015). Results from previous studies suggested that prolonged exposure to high number concentrations of UFP may be responsible for an impairment of lung function and/or development and exacerbation of respiratory diseases such as asthma or chronic obstructive pulmonary disease (COPD) (Terzano et al, 2010;Stanek et al, 2011;Slezakova et al, 2012;Ferreira et al, 2013;Carosino et al, 2015). In addition, children tend to be more susceptible to UFP toxicity when compared to adults, particularly due to their undeveloped immune and respiratory systems (Schwartz 2004;Foos et al, 2008).…”
mentioning
confidence: 99%
“…UFPs have been associated with a stronger toxicity when compared to PM2.5 and PM10 due to their proficiency for penetrating cell membranes (Penttinen et al 2001, Peters et al 1997, Semmler et al 2004. Moreover, results from previous studies suggest that long-term exposure to high number concentrations of UFPs may be responsible for an impairment of lung function, development and exacerbation of respiratory diseases such as asthma or chronic obstructive pulmonary disease, and may be even responsible for some carcinogenic activity, among other adverse health effects (Alessandrini et al 2009, Alessandrini et al 2006, Andersen et al 2010, Ferreira et al 2013, Stanek et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Varied delivery system engineering parameters, such as shape, size, materials, aggregation state, surface charge, chemical properties, formulation, etc. may each affect the toxicity profiles [110]. The small size of these new delivery systems imparts them with new physical and chemical properties different from conventional bulk drug powders [111].…”
Section: Fate Of Delivery Systemmentioning
confidence: 99%